2021
DOI: 10.3892/ol.2021.12710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of copy number variant and single nucleotide polymorphism of the programmed death‑ligand 1 gene, programmed death‑ligand 1 protein expression and therapy regimens on overall survival in a large group of Caucasian patients with non‑small cell lung carcinoma

Abstract: Anti-programmed death-1 or anti-programmed death-ligand 1 (PD-L1) blockade may be ineffective in some patients with non-small cell lung cancer (NSCLC) with high percentage of tumor cells with PD-L1 expression. In addition, immunotherapy may provide great benefits in patients without PD-L1 expression. The present study assessed PD-L1 protein expression by immunohistochemistry, copy number variation (CNV) of PD-L1 and two single nucleotide polymorphisms (SNPs), rs822335 and rs822336, in the promoter of PD-L1 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…This haplotype had T allele at rs822335 in addition to allele A at rs2297136. The impact of rs822335 on PD-L1 expression was investigated in tissue samples of NSCLC patients by Krawczyk et al ( 2019 ) and Grenada et al ( 2021 ). These authors detected a higher percentage of tumour cells presenting PD-L1 assessed by IHC in samples from patients with CC genotype compared to CT or TT genotypes (Krawczyk et al 2019 ; Grenda et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This haplotype had T allele at rs822335 in addition to allele A at rs2297136. The impact of rs822335 on PD-L1 expression was investigated in tissue samples of NSCLC patients by Krawczyk et al ( 2019 ) and Grenada et al ( 2021 ). These authors detected a higher percentage of tumour cells presenting PD-L1 assessed by IHC in samples from patients with CC genotype compared to CT or TT genotypes (Krawczyk et al 2019 ; Grenda et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of rs822335 on PD-L1 expression was investigated in tissue samples of NSCLC patients by Krawczyk et al ( 2019 ) and Grenada et al ( 2021 ). These authors detected a higher percentage of tumour cells presenting PD-L1 assessed by IHC in samples from patients with CC genotype compared to CT or TT genotypes (Krawczyk et al 2019 ; Grenda et al 2021 ). We carried out in silico analysis with RegulomeDB and 3DSNP 2.0 databases which showed that rs822335 was annotated with the enhancer state in the A549 cell line and Lung Fibroblast Primary Cells (NHLF), however, any potential binding site for transcription factor related to rs822335 was revealed.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a significant correlation between C/C genotype and OS in NSCLC patients is reported by Zhao et al as well as by Kang et al [ 69 , 70 ]. In contrast, no significant difference in survival outcomes based on rs822336 genotype is reported [ 48 , 71 , 72 ]. Here, we do not analyze the prognostic role of PD-L1 SNPs.…”
Section: Discussionmentioning
confidence: 99%